Growth variations within a farm of mussel (Mytilus galloprovincialis) held near fish cages: importance for the implementation of integrated aquaculture. (24th December 2013) - Irisarri, Jade; Cubillo, Alhambra M; Fernández‐Reiriz, María José; Labarta, Uxío
Abstract Fish farming releases extensive amounts of particulate organic waste that can be exploited by bivalves in integrated culture. We tested if mussels Mytilus galloprovincialis cultured at two depths (1 and 6 m) in a raft, moored 170 m from a fish farm had greater growth than bivalves held 550 m from the fish cages. Mussel growth was monitored monthly, covering the second phase of the culture, from thinning‐out to harvest (March to November 2011). We also studied if fish solid and dissolved nutrients increased the organic content of the seston and chlorophyll‐a levels near the fish cages through weekly samples. Results showed no differences in seston, chlorophyll and physiochemical characteristics of the water among rafts. Maximum growth and Condition Index (CI) occurred during spring–summer (April–August), when mussels had access to greater food quality and quantity. Mussels cultivated close to the cages showed similar shell length, weight and CI compared with mussels distant from the fish farm. Average shell length, meat dry weight and CI at harvest were 76.31 mm, 2.51 g and 23%. Bivalves cultured distant from the fish cages displayed 26% higher biomass than the other raft at the end of the experiment. Differences in biomass were explained by the significantly higher recruitment of mussel seed observed at the raft distant from the fish cages from June to November. The lack of a significant enhancement in growth of the bivalves cultured next to finfish is discussed.